Resilience levels based on individual characteristics of correctional nurses: preliminary study - Adisty Rose Artistin; Megah Andriany; Fani Kurnia Pusparini (International Journal of Nursing and Health Services (IJNHS), 2021)
Correctional nurses need resilience to face challenges in the workplace, such as stress from role ambiguity. This study aims to explore the level of resilience based on the individual characteristics of correctional nurses. This study used a cross-sectional method with 24 correctional nurses in Central Java as the participants. This study used a Nicholson McBride Resilience Questionnaire (NMRQ) questionnaire distributed via a google form. Data analysis using the cross-tabulation method. The results showed that nurses had a strong resilience level (45.83%). Based on gender, male nurses have higher resilience. Nurses aged 45-54 years have the most increased resilience. Nurses with undergraduate education have the highest resilience among other levels of education. In general, the correctional nurse resilience is in a Strong category. Based on individual characteristics, male nurses aged 45-54 years with a bachelor's degree have the highest resilience. Further study should be conducted to investigate correctional nurses' resilience process qualitatively, difficulties in work, how they deal with them, and the adaptation process